1987
DOI: 10.1055/s-2007-1006969
|View full text |Cite
|
Sign up to set email alerts
|

Chemotactic Arrangement of Axons Inside and Distal to a Venous Graft

Abstract: Experiments in rats, introducing the proximal and distal stumps of tibial and sural nerves into a vein graft, showed by acetylcholinesterase and toluidine blue staining that sensory and motor fibers mix inside the vein graft, but that nevertheless they are able to select their distal targets correctly. The authors' hypothesis is that surface membrane antigens of Schwann cells might be responsible for this chemotactic phenomenon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…In a further experiment, in 1987, they were able to demonstrate the selective chemotactic attraction for sensory and motor nerve fibres across an autologous vein graft shorter than 1 cm. 13 Selective chemotaxis was further demonstrated by &hi et al l4 and Maki.'' In 1984, Ide16 showed the possibility of using the basal lamina scaffold of the skeletal muscle to guide nerve regeneration.…”
Section: History Of Nerve Conduitsmentioning
confidence: 89%
See 1 more Smart Citation
“…In a further experiment, in 1987, they were able to demonstrate the selective chemotactic attraction for sensory and motor nerve fibres across an autologous vein graft shorter than 1 cm. 13 Selective chemotaxis was further demonstrated by &hi et al l4 and Maki.'' In 1984, Ide16 showed the possibility of using the basal lamina scaffold of the skeletal muscle to guide nerve regeneration.…”
Section: History Of Nerve Conduitsmentioning
confidence: 89%
“…In a further experiment, in 1987, they were able to demonstrate the selective chemotactic attraction for sensory and motor nerve fibres across an autologous vein graft shorter than 1 cm. 13 Selective chemotaxis was further demonstrated by &hi et al Mackinnon and DellonZ6 reported on nerve regeneration stumps of the damaged nerve; 3) contain all along its length substances exerting chemotactic attraction and giving a substratum for axonal progression, and 4) protect the regenerating axons against scar invasion. At present there are a number of problems associated with biological or biodegradable tubes: 1) the collapse of the tubes (especially veins) if the gap is too large, 2) the danger of early partial reabsorption with scar invasion, 3) the lack of chemotactic attraction for distances greater than 8-10 mm, and 4) the difficulty in matching muscle fibres with nerve fascicles at proximal and distal ends with loss of axons, when using fresh or predegenerated muscle.…”
Section: History Of Nerve Conduitsmentioning
confidence: 91%
“…Although autogenous nerve grafting is still considered the best current method for bridging peripheral nerve lesions with substance defect (Terzis et al 1997), several other grafting conduits (i.e., biological or synthetic tubes) have been studied experimentally for nerve repair (Lundborg et al 1981;Glasby et al 1986;Jimming et al 1986;Brunelli et al 1987;Rich et al 1989;Mackinnon and Dellon 1990;Chen et al 1994;Ansselin et al 1997). Previous studies showed that a new surgical procedure, named muscle-vein-combined grafting technique, could give very good results even for the repair of longdistance nerve defects (Brunelli et al 1993;Battiston et al 2000a,b).…”
Section: Introductionmentioning
confidence: 99%
“…7 After a long silence, it was reintroduced by a series of reports using the chamber models to examine axonal regeneration in an enclosed space, [8][9][10][11][12][13][14][15] including the concept of chemotaxis described by Cajal. 16 Since then, many experimental trials were done to examine the effects of prosthetic tubulization with a short gap on enhancing the selectivity of reinnervation, with positive [17][18][19][20][21][22][23] and negative 24,25 results.…”
mentioning
confidence: 99%